IMMUNE RESPONSE MODULATION TO DPT (DIPHTHERIA, PERTUSSIS, TETANUS) VACCINE BY NDL FROM CALOTROPIS PROCERA - PRASHANT BAGHERWAL; LALIT MACHAWAL (International Journal of Pharma and Bio Sciences, 2013)
Immunomodulation with adjuncts is novel pharmaceutical intervention which explores its new therapeutical dimensions in medical field. Calotropis procera (Family Asclepiadaceae) was evaluated in laboratory animals immunized with DPT (Diphtheria, Pertussis, Tetanus) vaccine for its immunopotentiation effect. NDL (non-dialyzable latex) latex of Calotropis procera (150 mg/kg/day, p.o.) was evaluated for its immunopotentiation effect. The immunostimulation was evaluated using serological and hematological parameters. Treatment of immunized animals with NDL (150 mg/kg/day, p.o.) for 15 days resulted in a significant increase of antibody titers to B. pertussis (P < 0.05). B. pertusis BLC-216 strain were used to immunized animals and after that animals were observed for 14 days (treated and untreated) were challenged by B. pertusis BLC-216 and the animals were observed for two weeks. That indicate the NDL (150 mg/kg/day, p.o.) treated animals groups represent significant enhancement of antibody titers as compared to controlled / untreated animals after challenge (P < 0.05). Immune protection against intra-cerebral challenge of B. pertussis live cells was evaluated on behailf of degree of sickness, paralysis and death. Reduced mortality accompanied with overall improved health status was observed in treated animals after intracerebral challenge of B. pertussis indicating the development of protective immune response.The NDL of Calotropis procera also offers direct therapeutic benefits resulting in reduced morbidity and mortality of experimental animals. Present study indicates application of NDL of Calotropis procera act as a mild immunopotentiating agent with possible applications in immunopharma industry.